Diuretic Resistance in Acute Decompensated Heart Failure: A Challenging Clinical Conundrum. Issue 4 (October 2017) - Reed, Brent N.; Devabhakthuni, Sandeep
Abstract : Most patients with acute decompensated heart failure (ADHF) present with signs and symptoms of volume overload, and those with a significant history of diuretic exposure may demonstrate varying degrees of diuretic resistance. Although this phenomenon is commonly reported, no consensus definition exists and recommendations regarding an optimal therapeutic approach remain limited. Optimizing the use of intravenous (IV) loop diuretic therapy is the most common initial approach, and therapy may be augmented by the addition of a thiazide-type diuretic or an IV vasodilator. Patients whose resistance to diuretic therapy is due to low cardiac output may require inotropic therapy, and other options (eg, ultrafiltration and vasopressin antagonists) may be considered in select populations. The purpose of this review is to describe diuretic resistance and its underlying mechanisms in ADHF, as well as the most commonly employed strategies for overcoming it. A stepwise approach to managing volume overload in patients with ADHF and diuretic resistance is also provided.